Membangun ekonomi Biru yang Berkelanjutan: Analisis Penerapan Blue Accounting pada Kawasan Ekonomi Khusus (KEK) Kuta Mandalika - Utami, Luh; Yuliandari, Rini; Santanu, Ketut Oka; Aswaldi, Haykal (LPPM Institut Pendidikan Nusantara Global, 2025)
This study analyzes the application of blue accounting as an instrument of environmental accountability to support sustainable blue economy development in the Kuta Mandalika Special Economic Zone (SEZ). Blue accounting is defined as a system for recording and reporting economic activities that integrates social, ecological, and economic impacts. This research addresses the limited empirical studies connecting community-based blue economy practices with environmental accounting in Indonesia’s coastal tourism sector. Using a qualitative grounded theory approach, data were collected through in-depth interviews, field observations, and document analysis. Analysis was conducted through three stages, open coding, axial coding, and selective coding, to develop a substantive theory of blue accounting implementation at the community level. Findings reveal that blue economy practices in Mandalika have emerged through strong ecological awareness among local communities and business actors, although formal blue accounting remains limited. Through thematic analysis, three indicator groups were identified: economic (cleaning costs and conservation investment), social (community participation and environmental education), and ecological (waste management and coastal rehabilitation). These findings extend the concept of blue accounting as community-based socio-ecological accountability distinct from conventional environmental accounting.Policy recommendations derived directly from the findings include enhancing environmental accounting literacy for small enterprises, developing activity-based reporting guidelines, strengthening multi-stakeholder collaboration (pentahelix), and initiating community-based pilot projects. The study contributes theoretically by expanding the understanding of blue accounting within sustainable tourism, and practically by offering indicator frameworks and strategies for its implementation in other coastal areas of Indonesia.